Effectiveness of Giving Secang Wood Extract (Caesalpinia Sappan L) Against IL-6 And IL-10 Levels in Balb / C Mice With Vulvovaginalis Candidiasis - Sri Wahyu; Firdaus Hamid; Mochammad Hatta; Khairuddin Djawad; Agussalim Bukhari; Rosdiana Natzir; Alfina Baharuddin (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this study was to test the effectiveness of secang wood extract (Caesalpinia sappan L) onIL-6 and IL-10 expression in Balb / c mice with vulvovaginalis candidiasis. This type of research is anexperimental laboratory, with a control group design using experimental animals as research objects. Theresearch subjects were BALB / c mice weighing 35-40 grams, aged 10-12 weeks, the number of experimentalanimals needed in this study was 18 for 3 random groups, each group being 6. Analysis and data processingusing the excel program SPSS Repeated ANOVA Test was used to measure differences in cytokine levels.IL-6 levels in group 1 (control) where the value of IL-6 expression after infection (H1) was 4309.40 pg /mL(IQR value 3803.8-4963.5) after treatment (H7) in the control group increased by 5578.12 pq / mL (IQR5330.3 - 6162.9). In group 2 that were given fluconazole and secang wood extract, IL-6 levels tended todecrease by 3516.4 pq / mL (IQR: 3070.4-4061.6) Secang wood after infection decreased from 3417.34 pq/ mL to 2782.97 pq / mL after treatment. In Group 2 that was given fluconazole and secang wood extract,IL-10 levels increased by 1414.8 pq / ml (IQR: 1061.7- 3158) after infection, to 3268.35 pq / ml (IQRvalue: 1789.9-3709.6) after treatment. given secang wood after infection increased from 2032.67 pq / ml to3091.83 pq / mL after treatment. The p value is 0.008. Obtained the effect of secang wood extract in reducinglevels of Interleukin 6 and can increase the value of IL-10 levels after administration of secang wood extracton candidiasis vulvovaginalis